The effectiveness of the idea harvesting strategy in acquiring legal knowledge and refereeing performance in volleyball among students of the Faculty of Education and Sports Sciences at Koya University. - Amin, Prof. Dr. Rebaz Majeed Amin (Sulaimani Journal for Humanities, 2025)
The research aims to identify: - The differences between the students of the experimental group that studied according to the strategy (harvesting ideas) and the students of the control group that studied according to the method used in the post-test of the scale of legal knowledge and refereeing performance in volleyball. The research population was represented by fourth-year students at the College of Physical Education and Sports Sciences at Koya University. The sample was selected by a simple random method and was distributed into two groups: an experimental group that studied according to the idea harvesting strategy and a control group that studied according to the method used in teaching. The research tool was determined from a measure of legal knowledge and volleyball refereeing performance. The research tools were determined from the cognitive test for legal subjects in volleyball, which consists of (40) items and which was designed by (Amjad Ali, 2015), and the observation form for evaluating the performance of the first referee, which was designed by (Yassin and Shaima, 2007). Equivalence was conducted between the two research groups in variables. (Age, parental achievement, intelligence,). Then the experiment began to be implemented by teaching the experimental group according to the idea harvesting strategy, while the control group studied according to the strategy used by the teacher. After completing the experiment, a knowledge achievement test for international volleyball law was conducted, and a refereeing performance test was conducted through Using a special form for direct observation by the arbitrators, and after collecting the data and processing it with appropriate statistical means represented by the t-test for independent samples and extracting the effect size, a set of conclusions were reached, including: - The strategy of harvesting ideas had a significant impact on cognitive achievement and refereeing performance of international law in volleyball, which was applied to the experimental group, and its superiority over the control group that studied according to the strategy used by the teacher. - The researcher recommended emphasizing the use of the idea harvesting strategy because of its impact on the process of analyzing and linking the legal materials to volleyball.
Keywords: harvesting ideas; legal knowledge; arbitration performance